New perspectives on the induction and acceleration of immune-associated thrombosis by PF4 and VWF - Liu, Zhi-Yan; Sun, Min-Xue; Hua, Man-Qi; Zhang, Han-Xu; Mu, Guang-Yan; Zhou, Shuang; Wang, Zhe; Xiang, Qian; Cui, Yi-Min (Frontiers in Immunology, 2023)
Platelet factor 4 (PF4), also known as chemokine (C-X-C motif) ligand 4 (CXCL4), is a specific protein synthesized from platelet α particles. The combination of PF4 and heparin to form antigenic complexes is an important mechanism in the pathogenesis of heparin-induced thrombocytopenia (HIT), but vaccine-induced immune thrombotic thrombocytopenia (VITT) related to the COVID-19 vaccine makes PF4 a research hotspot again. Similar to HIT, vaccines, bacteria, and other non-heparin exposure, PF4 can interact with negatively charged polyanions to form immune complexes and participate in thrombosis. These anions include cell surface mucopolysaccharides, platelet polyphosphates, DNA from endothelial cells, or von Willebrand factor (VWF). Among them, PF4–VWF, as a new immune complex, may induce and promote the formation of immune-associated thrombosis and is expected to become a new target and therapeutic direction. For both HIT and VITT, there is no effective and targeted treatment except discontinuation of suspected drugs. The research and development of targeted drugs based on the mechanism of action have become an unmet clinical need. Here, this study systematically reviewed the characteristics and pathophysiological mechanisms of PF4 and VWF, elaborated the potential mechanism of action of PF4–VWF complex in immune-associated thrombosis, summarized the current status of new drug research and development for PF4 and VWF, and discussed the possibility of this complex as a potential biomarker for early immune-associated thrombosis events. Moreover, the key points of basic research and clinical evaluation are put forward in the study.